Respuesta :
f(x) - g(x) = 3x² + x - 3 - (x² - 5x + 1)
f(x) - g(x) = 3x² + x - 3 - x² + 5x - 1
f(x) - g(x) = 3x² - x² + x + 5x - 3 - 1
f(x) - g(x) = 2x² + 6x - 4
f(x) - g(x) = 3x² + x - 3 - x² + 5x - 1
f(x) - g(x) = 3x² - x² + x + 5x - 3 - 1
f(x) - g(x) = 2x² + 6x - 4
Substitute the two functions according to a given condition of function:
f(x) - g(x) = 3x² + x - 3 - (x² - 5x + 1)
= 3x² + x - 3 - x² + 5x - 1
= 2x² + 6x - 4 or 2(x² + 3x - 2)
f(x) - g(x) = 3x² + x - 3 - (x² - 5x + 1)
= 3x² + x - 3 - x² + 5x - 1
= 2x² + 6x - 4 or 2(x² + 3x - 2)